تعليم الترجمة في ضوء نموذج كايزر ) )Keiser’s Model وتطبيقه في مركز لسان عربي للترجمة - Mohammad Kholison (Lugawiyyat, 2020)
Translation is the communication of meaning from one language (the source) to another language (the target). Translation refers to written information, whereas interpretation refers to spoken information.The purpose of translation is to convey the original tone and intent of a message,taking into account cultural and regional differences between source and target languages.Translation is very necessary to get information from any resources in foreignlanguages. Therefore, translation is the way of the translator who has the ability to understand the method and the process to establish the information from foreign language.Lisan Arabi for translation, one of the language publishers, endeavors to be an inner cicle for learners and advisor of translation. The aim of this program is to produce the good translation that is able to be published and distributed to academics and scholars.